MERANCANG MANAJEMEN BISNIS SYARIAH AGRIBISNIS DI DESA CIMANGGU I, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Ermi Suryani; Rifki Imamudin (SAHID EMPOWERMENT JOURNAL, 2022)
Agriculture is a very important component of the country because it is through agriculture that all people in Indonesia fulfill their basic needs in the form of food. These needs precede the needs for clothing (clothing) and boards (shelter). One of the fulfillments of agricultural needs is for agribusiness, and of course management is needed, or more specifically, sharia business management in managing abundant natural resources so that they grow and continue to function as they should. The presence of agribusiness management is so that agriculture can develop and progress. Agribusiness management needs to be addressed or managed in a sharia business management, and therefore agribusiness sharia business management needs to be designed in community service activities in Cimanggu I Village, Cibungbulang District, Bogor Regency.